Regulation of pigmentation by microRNAs: MITF‐dependent microRNA‐211 targets TGF‐β receptor 2. (7th January 2015) - Dai, Xiaodan; Rao, Chunbao; Li, Huirong; Chen, Yu; Fan, Lilv; Geng, Huiqin; Li, Shuang; Qu, Jia; Hou, Ling
Summary There is growing evidence that microRNAs are important regulators of gene expression in a variety of cell types. Using immortalized cell lines and primary neural crest cell explants, we show that microRNA‐211, previously implicated in the regulation of melanoma proliferation and invasiveness, promotes pigmentation in melanoblasts and melanocytes. Expression of this microRNA is regulated by the key melanocyte transcription factor MITF and regulates pigmentation by targeting the TGF‐β receptor 2. Transfection with pre‐miR‐211 precursor molecules in melb‐a and melan‐a cells leads to a decrease in the expression of TGF‐β receptor 2 and reduces the TGF‐β signaling‐mediated downregulation of two melanogenic enzymes, tyrosinase and tyrosinase‐related protein 1. Conversely, downregulation of microRNA‐211 using specific microRNA inhibitors has the opposite effects. It appears, therefore, that microRNA‐211 serves as a negative regulator of TGF‐β signaling which is known to play a important roles in vivo in melanocyte stem cell maintenance and pigmentation.